Radiation resistance of a cylindrical antenna radiating in weakly ionized plasma† - Singh K.P.; Shukla P.K.; Misra K.D. (My University, 2025)
The electromagnetic and electroacoustic field components of cylindrical antenna radiating in weakly ionized plasma are obtained. Assuming the plausible current distribution, expressions for radiation resistances and radiated power of electromagnetic and electroacoustic field on the wave are obtained. The effect of electron collision on the electroacoustic and electromagnetic radiation resistances and total power radiated is discussed. It is concluded that for precise communication purposes an account of the radiating surroundings should be made. © 1972, Taylor & Francis Group, LLC.